Graphene quantum dots-incorporated cathode buffer for improvement of inverted polymer solar cells - Li, Chang Ming (2016)
Graphene quantum dots (GQDs) are an emerging class of nanomaterials with unique photonic and electric properties. In this study, GQDs were prepared by a facile, inexpensive and high-yield hydrothermal method and were further used as a cathode buffer additive for inverted polymer solar cells due to a wide band gap (~3.3 eV) and well-matched energy level between GQDs–cesium carbonate (GQDs–Cs2CO3) modified indium tin oxide (3.8 eV) and high occupied molecular orbit of [6,6]-phenyl-C61-butyric acid methyl ester (3.7 eV). In comparison to inverted polymer solar cells using cesium carbonate (Cs2CO3) buffer layer, the power conversion efficiency of GQDs–Cs2CO3 based device showed 22% enhancement from 2.59% to 3.17% as a result of enhanced exciton dissociation and suppressed free charge recombination at cathode/polymer active layer interface by GQDs. This work provides a new application of GQDs in organic electronic devices.